(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article is devoted to the possibility of studying the advanced experience of developed foreign countries in the field of effective organization of tax administration and its application in the conditions of Uzbekistan. The main purpose of the study is to identify the main aspects of advanced experiments and develop recommendations for their use in the tax administration of Uzbekistan. Also ,the article mainly studied the tax administration of foreign developed countries and covered the issues of further development and elimination of moammos in Uzbekistan on the basis of their experience. The results of the study in this article are of practical importance for the tax authorities of Uzbekistan and can serve as the basis for the development of strategies for improving tax administration in the country.